2022
DOI: 10.12669/pjms.38.4.5343
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Articaine vs Lignocaine for infiltration anaesthesia during primary molar extractions

Abstract: Objectives: The purpose of this systematic review was to evaluate if articaine has better efficacy as compared to lignocaine when used for infiltration anaesthesia for primary molar extractions. Methods: The electronic databases of PubMed, Embase, Scopus, BioMed Central, CENTRAL, and Google Scholar were searched up to August 2020. Randomized controlled trials on paediatric patients comparing the infiltration of articaine with lignocaine for extraction of primary molar were included. Pain of extraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Nevertheless they found that articaine was more effective than lidocaine during extraction with buccal infiltration anesthesia [ 25 ]. Chen et al [ 26 ] stated in their review that a single buccal injection for primary molar extractions eliminates painful palatal injections and provides a potential advantage during treatment in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless they found that articaine was more effective than lidocaine during extraction with buccal infiltration anesthesia [ 25 ]. Chen et al [ 26 ] stated in their review that a single buccal injection for primary molar extractions eliminates painful palatal injections and provides a potential advantage during treatment in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%